Modelling the climate change adaptation potential of notillage maize systems in southern Africa - Rusinamhodzi, L.; Berre, D.; Thierfelder, C.; Ridaura, S.L.; Corbeels, M. (2025)
Southern Africa is a hotspot of climate change where smallholder farmers are particularly threatened because they largely depend on rainfed agriculture for their livelihoods. The objective of the study was to assess the potential of two main principles (no-tillage and crop residue retention) of conservation agriculture (CA) and nitrogen (N) fertilizer management to mitigate the negative effects of future climate (2021–2060) on maize (Zea mays L.) productivity using the Agricultural Production Systems Simulator (APSIM). Two tillage practices were considered in the simulations, i.e. the conventional practice of tillage with removal of crop residues (CP) and NT (no-tillage and crop residue mulching), as well as three rates of N input (0, 30, 90 kg ha−1) on mono-cropped continuous maize. Simulations were run for future climate generated by an ensemble of 17 global circulation models (GCMs) using two extreme emission scenarios based on Representative Concentration Pathways (RCP2.6 and RCP8.5) for southern Africa. Results from the simulations suggest that NT management is not more beneficial in the future (2051–2060) than in the current climate, and there is no evidence to support its ability to mitigate the climate change impacts at the study sites, because the effects are principally exerted through increased temperatures. Simulations further show that increased fertilizer N inputs could drastically increase maize productivity, but with increased vulnerability to climate change. Improved crop management practices such a NT need to be combined with improved crop genotypes tolerant to multiple stresses such as drought and heat to maximize resilience under future climatic conditions.